2019
DOI: 10.1101/558080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Promote Prostate Cancer Malignancy via Metabolic Rewiring and Mitochondrial Transfer

Abstract: Cancer-associated fibroblasts (CAFs) are the major cellular stromal component of many solid tumors. In prostate cancer (PCa), CAFs establish a metabolic symbiosis with PCa cells, contributing to cancer aggressiveness through lactate shuttle. In this study, we report that lactate uptake alters the NAD + /NADH ratio in the cancer cells, which culminates with SIRT1-dependent PGC-1α activation and subsequent enhancement of mitochondrial mass and activity. The high exploitation of mitochondria results in tricarboxy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 52 publications
1
58
0
Order By: Relevance
“…Cancer-associated fibroblasts are known to play a significant role in tumor progression and metastasis also through metabolic rewiring [ 156 , 157 ]. Higher levels of CAFs are associated with larger tumors and shorter survival time [ 158 ].…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Cancer-associated fibroblasts are known to play a significant role in tumor progression and metastasis also through metabolic rewiring [ 156 , 157 ]. Higher levels of CAFs are associated with larger tumors and shorter survival time [ 158 ].…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…The PCSCs microenvironment is composed of different stromal cell populations while the most abundant cell types are cancer-associated fibroblasts (CAFs) and tumor-associated macrophages (TAMs), either resident or recruited from circulatory system 11 . It has been widely reported that CAFs exert a mandatory role in prostate cancer progression as they metabolically sustain prostate cancer cell survival and growth, recruit inflammatory and immune cells, and promote cancer cells stemness and EMT, thereby favoring metastatic dissemination 12,13 . As the most highly infiltrative immune cell population within the TME, TAMs account for 30-50% of the tumor mass 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It fuels the tricarboxylic acid (TCA) cycle and subsequent mitochondrial respiration. CAFs can directly provide cancer cells with pyruvate (as shown in lymphoma [ 6 ]), and also indirectly by providing lactate (as shown in prostate cancer [ 7 , 8 ] and breast cancer [ 4 , 9 ]) or alanine (as shown in pancreatic cancer [ 10 ]), both latter metabolites being transformed into pyruvate via active lactate dehydrogenase and alanine aminotransferase, respectively. CAFs also fuel malignant cells with glutamine in glutamine-deprived conditions (as shown in ovarian cancer [ 11 ]), which is transformed into glutamate and then alpha-ketoglutarate to enter the TCA cycle and generate biosynthetic precursors.…”
Section: Cafs Sustain Cancer Cells Mitochondriamentioning
confidence: 99%
“…More precisely, these metabolites fuel malignant cells’ TCA cycle, which feeds biosynthetic pathways to produce key precursors such as lipids, proteins and nucleic acids, thus promoting primary and metastatic cell growth [ 7 , 10 , 11 ]. In some of the studies, TCA cycle modulation induced by CAFs even leads to higher malignant cell oxygen consumption, reflecting mitochondrial respiration increase [ 8 , 10 ]. In addition, a CAFs-induced increase in TCA cycle activity is associated with primary patient malignant cell survival [ 6 ].…”
Section: Cafs Sustain Cancer Cells Mitochondriamentioning
confidence: 99%